Hope on the plains [large type] - Byler, Linda (Byler, Linda. Dakota series ;, 2019)
"Hannah, a feisty young Amish woman, lives on her family's farm in North Dakota. As the local Amish community begins to thrive, a terrible drought and a windmill fire devastate their business and the community. Hannah must choose whether to stay in North Dakota or move back to Lancaster, Pennsylvania, with the other Amish families that are leaving"--